Atopic dermatitis in West Highland white terriers – part I: natural history of atopic dermatitis in the first three years of life. Issue 2 (23rd October 2019) - Favrot, Claude; Fischer, Nina; Olivry, Thierry; Zwickl, Lena; Audergon, Sabrina; Rostaher, Ana
Abstract : Background: Canine atopic dermatitis (cAD) is a common allergic skin disease that is known to affect individuals early in life; the natural history of its initial development has not been documented. Some breeds such as West Highland white terriers (WHWTs) are highly predisposed to cAD. Objectives: To follow 100 WHWT puppies during their first three years and to record the onset of clinical signs of cAD. Animals: One hundred and eight puppies from 29 litters were included and 90 were followed for three years. Methods and materials: Puppies were examined initially while with their breeders. After adoption, the owners were contacted twice each year and dogs were examined by veterinarians if signs compatible with cAD were detected; diagnosis of cAD was by two different definitions. The onset, location of the clinical signs and severity of cAD, as well as co‐morbidities were recorded. Results: The prevalence of cAD in the cohort was 52%. Most affected dogs (60%) developed signs of cAD during their first year of life and males were over‐represented. The location of clinical signs mirrored those of previous descriptions. The severity of cAD was mild in 36% and severe in 13% of affected WHWTs. Dogs with cAD often exhibited other atopic diseases, but only gastro‐intestinal signs were significantly different between WHWTs with and without cAD. Adverse reaction to foods was diagnosed in 24% of dogs. Conclusion and clinical importance: This longitudinal study of puppies from a predisposed breed sheds new light on the early development of cAD in WHWTs. Abstract : Background – Canine atopic dermatitis (cAD) is a common allergic skin disease that is known to affect individuals early in life; the natural history of its initial development has not been documented. Some breeds such as West Highland white terriers (WHWTs) are highly predisposed to cAD. Objectives – To follow 100 WHWT puppies during their first three years and to record the onset of clinical signs of cAD. Conclusion and clinical importance – This longitudinal study of puppies from a predisposed breed sheds new light on the early development of cAD in WHWTs. Résumé: Contexte: La dermatite atopique canine (DAC) est une dermatose allergique fréquente qui est connue pour atteindre les sujets dès le jeune âge; le développement précoce de l'atteinte n'a pas été décrit. Certaines races, comme le West Highland white terrier (WHWTs), sont hautement prédisposées à la DAC. Objectifs: Suivre 100 WHWT chiots au cours de leurs trois premières années de vie et caractériser l'apparition des premiers signes cliniques de DAC. Sujets: Cent huit chiots issus de 29 portées ont été inclus et 90 ont été suivis pendant trois ans. Matériels et méthodes: Les chiots ont été examinés initialement chez l'éleveur. Après adoption, les propriétaires ont été contactés deux fois par an, et les chiens ont été examinés par le vétérinaire si des signes compatibles avec une DAC étaient détectés; le diagnostic de DAC était défini par deux méthodes. L'apparition, la localisation des signes cliniques et la sévérité de la DAC, ainsi que les comorbidités, ont été enregistrés. Résultats: La prévalence de DAC dans la cohorte était de 52%. Les chiens les plus atteints (60%) ont développé des signes cliniques de DAC au cours de leur première année de vie et les mâles étaient surreprésentés. La localisation des signes cliniques correspondait aux descriptions antérieures. La sévérité de DAC était modérée pour 36% et sévère pour 13% des WHWTs atteints. Les chiens avec DAC montraient souvent d'autres maladies atopiques, mais seuls les signes gastro‐intestinaux étaient significativement différents entre les WHWTs avec et sans DAC. Une réaction indésirable à l'alimentation était diagnostiquée pour 24% des chiens. Conclusion et importance clinique: Cette étude longitudinale des chiots d'une race prédisposée jette une nouvelle lumière que le développement précoce de la DAC chez le WHWT. Resumen: Introducción: la dermatitis atópica canina (cAD) es una enfermedad alérgica cutánea común que se sabe que afecta a las animales a edades tempranas; La historia natural de su desarrollo inicial no ha sido documentada. Algunas razas como los West Highland White Terriers (WHWT) están altamente predispuestas a la cAD. Objetivos: seguimiento de 100 cachorros de WHWT durante sus primeros tres años y registrar la aparición de signos clínicos de cAD. Animales: se incluyeron ciento ocho cachorros de 29 camadas y 90 fueron seguidos durante tres años. Métodos y materiales: los cachorros fueron examinados inicialmente mientras estaban con sus criadores. Después de la adopción, se contactó a los propietarios dos veces al año y los veterinarios examinaron a los perros si se detectaban signos compatibles con cAD; el diagnóstico de cAD se realizó mediante dos definiciones diferentes. Se registró el inicio, la localización de los signos clínicos y la gravedad de la cAD, así como las comorbilidades. Resultados: la prevalencia de cAD en la cohorte fue del 52%. La mayoría de los perros afectados (60%) desarrollaron signos de cAD durante su primer año de vida y los perros macho estaban sobrerrepresentados. La localización de los signos clínicos refleja la de las descripciones anteriores. La intensidad de la cAD fue leve en el 36% y severa en el 13% de los WHWT afectados. Los perros con cAD a menudo exhibieron otras enfermedades atópicas, pero solo los signos gastrointestinales fueron significativamente diferentes entre WHWT con y sin cAD. Se diagnosticó reacción adversa a los alimentos en el 24% de los perros. Conclusión e importancia clínica: este estudio longitudinal de cachorros de una raza predispuesta aporta nueva información sobre el desarrollo temprano de cAD en WHWTs. Zusammenfassung: Hintergrund: Die canine atopische Dermatitis (cAD) ist eine häufige allergische Hauterkrankung, die bekanntermassen Individuen früh in ihrem Leben beeinflusst; die Naturgeschichte ihrer ursprünglichen Entwicklung ist bislang nicht dokumentiert. Einige Rassen, wie der West Highland White Terrier (WHWTs) sind höchst prädisponiert für cAD. Ziele: Das Ziel bestand darin 100 WHWT Welpen während ihrer ersten drei Lebensjahre zu verfolgen und den Beginn von klinischen Zeichen einer cAD schriftlich festzuhalten. Tiere: Einhundertacht Welpen aus 29 Würfen wurden in die Studie aufgenommen und 90 wurden drei Jahre lang verfolgt. Methoden und Materialien: Die Welpen wurden ursprünglich während sie noch bei den Züchtern waren, untersucht. Nach der Adoption durch die neuen BesitzerInnen, wurden diese zweimal jährlich kontaktiert und die Hunde wurden falls Anzeichen auftraten, die mit einer cAD kompatibel waren, von TierärztInnen untersucht; die Diagnose einer cAD erfolgte mithilfe zweier unterschiedlicher Definitionen. Das Auftreten, die Lokalisation der klinischen Zeichen und die Schwere der cAD sowie Begleitkrankheiten wurden notiert. Ergebnisse: Die Prävalenz der cAD in der Kohorte betrug 52%. Die meisten betroffenen Hunde (60%) entwickelten Anzeichen einer cAD in ihrem ersten Lebensjahr, wobei männliche Tiere überrepräsentiert waren. Die Lokalisation der klinischen Zeichen spiegelte jene von früheren Beschreibungen wider. Die Schwere der cAD war bei 36% mild und bei 13% der betroffenen WHWTs ausgeprägt. Hunde mit cAD zeigten oft auch andere atopische Erkrankungen, aber ausschließlich gastrointestinale Anzeichen waren signifikant unterschiedlich zwischen WHWTs mit und ohne cAD. Es wurden bei 24% der Hunde adverse Reaktionen auf Futter diagnostiziert. Schlussfolgerung und klinische Bedeutung: Diese longitudinale Studie von Welpen einer prädisponierten Rasse wirft ein neues Licht auf die frühe Entwicklung von cAD bei WHWTs. 要約: 背景: 犬アトピー性皮膚炎(cAD)は、一般的なアレルギー性皮膚疾患で、若齢期より罹患することが知られている。しかし、cADの初期発生に対する自然歴は報告されていない。ウエスト・ハイランド・ホワイト・テリア(WHWT)などの一部の犬種は、cADに対し高い素因を持つ。 目的: 本研究の目的は、100頭のWHWTの生後3年間を追跡し、cADの臨床徴候の発症を記録することである。 被験動物: 29頭の同腹仔から産まれた108頭の子犬を包含し、90頭を3年間追跡した。 材料と方法: 最初は子犬をブリーダーとともに検査した。養子縁組後、飼い主に毎年2回連絡を取り、cADと互換性のある兆候が検出された場合、獣医師が犬を検査した。 cADの診断は2つの異なる定義によるものであった。発症、臨床徴候の分布、およびcADの重症度、ならびに併発疾患を記録した。 結果: コホートにおけるcADの有病率は52%であった。罹患犬のほとんど(60%)は、生後1年以内にcADの徴候を発症し、雄が大きな割合を占めた。臨床徴候の分布は、既存の報告を反映していた。 cADの重症度は、罹患したWHWTの36%で軽度で、13%で重度であった。 cADを有する犬はしばしば他のアトピー性疾患を示したが、cADの有無によるWHWT間では胃腸兆候のみが有意に異なっていた。 24%の犬において、食物有害反応を診断した。 結論と臨床的重要性: 素因のある犬種の子犬に関する本縦断的研究は、WHWTにおけるcADの初期発生に新たな光を当てる。 摘要: 背景: 犬异位性皮炎(cAD)是一种常见的过敏性皮肤病, 已知在生命早期就会对个体产生影响。其最初发展的自然病史尚无报道。某些品种, 例如西部高地白㹴(WHWT)易患cAD。 目标: 跟踪100只WHWT幼犬在出生后三年的情况, 并记录cAD的临床体征。 动物: 包括来自29窝的108只幼犬, 对其中90只进行了3年的跟踪调查。 方法和材料: 对繁殖者饲养的幼犬进行首次检查。被领养后, 兽医每年与主人联系两次, 对犬进行检查, 以期发现是否存在cAD症状。cAD的诊断有两种不同的定义。 记录cAD的发作、临床体征和严重程度, 以及并发症。 结果: 这些犬中cAD的患病率为52%。大多数患犬(60%)在其生命的第一年就出现了cAD症状, 且大多数为雄性。临床体征的位置与先前描述相符。WHWT患犬cAD的严重程度为36%轻度, 13%重度。 有cAD的犬经常表现出其他异位性疾病, 但是有和没有cAD的WHWT之间只有胃肠道症状显著不同。24%的犬被诊断出食物不良反应。 结论和临床意义: 对这种易感品种的幼犬进行纵向研究, 为WHWT中cAD的早期发展增加了新内容。 Resumo: Contexto: A dermatite atópica canina (DAC) é uma dermatopatia alérgica da pele, que afeta os indivíduos no início da vida; a história natural de seu desenvolvimento inicial ainda não foi documentada. Algumas raças, como os West Highland white terriers (WHWTs), são altamente predispostos ao DAC. Objetivos: Acompanhar 100 filhotes WHWT durante seus primeiros três anos de vida e registrar o aparecimento de sinais clínicos de DAC. Animais: Cento e oito filhotes de 29 ninhadas foram incluídos e 90 foram acompanhados por três anos. Métodos e materiais: Os filhotes foram examinados inicialmente enquanto viviam ainda com seus criadores. Após a adoção, os donos eram contatados duas vezes por ano e os cães eram examinados por veterinários se fossem detectados sinais compatíveis com o DAC; O diagnóstico de DAC foi realizado por duas definições diferentes. Foram registrados o início do surgimento dos sinais clínicos, a sua localização e a gravidade da DAC, bem como as comorbidades. Resultados: A prevalência de DAC na coorte foi de 52%. Os cães mais afetados (60%) desenvolveram sinais de DAC durante o primeiro ano de vida e os machos estavam super‐representados. A localização dos sinais clínicos espelhava a das descrições anteriores. A severidade do DAC foi leve em 36% e grave em 13% dos casos de WHWT afetados. Cães com DAC frequentemente exibiam outras doenças atópicas, mas apenas os sinais gastrointestinais foram significativamente diferentes entre os WHWTs com e sem DAC. Reação adversa aos alimentos foi diagnosticada em 24% dos cães. Conclusão e importância clínica: Este estudo longitudinal de filhotes de uma raça predisposta lança uma nova luz sobre o desenvolvimento inicial de DAC em WHWTs